Perancangan dan Pembuatan Sistem Informasi Penggajian Karyawan Pada LA Beaute Skincare Medan - Rivon Fotriyodi (Jurnal Multidisiplin Indonesia, 2023)
La Beaute Skincare is a private company that operates in the beauty services sector with a payroll system that is not yet effective because salary and commission calculation errors often occur because the salary calculation process is still manual using a calculator. There is a delay in paying employee salaries due to the long time required to calculate employee commissions. There is no proper recording of employee loans because loan data is only recorded in a memo so it is often forgotten when calculating employee salaries. It is difficult to find documents related to payroll because they are still mixed with other documents. This research was conducted with a direct survey at La Beaute Kincare using library methods, observation, interviews and document analysis. The database was created using MYSQL and Microsoft Visual Studio 2008 as the programming language. Thus, the final result to be achieved with this employee payroll information system is that it can make it easier to resolve problems in current business processes and help La Beatu Skincare to produce reports that are more accurate and relevant in decision making.